Кризис советского метанарратива (современная ситуация восточнославянских литератур) - Poliszczuk, Jarosław (Acta Polono-Ruthenica, 2018)
The author of the article revises the process of gradual deconstruction of soviet metanarrative in literature of Russia, Belorussia and Ukraine after 1991st. Each of those literatures built its own identity, which had to replace soviet cultural discourse. That process was contradictory, but still quite productive. Contemporary post-soviet literature is in boundary situation. It means that the crisis of the transition period has not been completely overcome. The main problems in creating of the national narratives are neo-imperial (in Russia) or neo-colonial (in Belorussia and Ukraine) tendencies.